Violence prevention accelerators for children and adolescents in South Africa: A path analysis using two pooled cohorts. - Lucie D Cluver; William E Rudgard; Elona Toska; Siyanai Zhou; Laurence Campeau; Yulia Shenderovich; Mark Orkin; Chris Desmond; Alexander Butchart; Howard Taylor; Franziska Meinck; Lorraine Sherr (PLoS Medicine)
Background The INSPIRE framework was developed by 10 global agencies as the first global package for preventing and responding to violence against children. The framework includes seven complementary strategies. Delivering all seven strategies is a challenge in resource-limited contexts. Consequently, governments are requesting additional evidence to inform which 'accelerator' provisions can simultaneously reduce multiple types of violence against children. Methods and findings We pooled data from two prospective South African adolescent cohorts including Young Carers (2010-2012) and Mzantsi Wakho (2014-2017). The combined sample size was 5,034 adolescents. Each cohort measured six self-reported violence outcomes (sexual abuse, transactional sexual exploitation, physical abuse, emotional abuse, community violence victimisation, and youth lawbreaking) and seven self-reported INSPIRE-aligned protective factors (positive parenting, parental monitoring and supervision, food security at home, basic economic security at home, free schooling, free school meals, and abuse response services). Associations between hypothesised protective factors and violence outcomes were estimated jointly in a sex-stratified multivariate path model, controlling for baseline outcomes and socio-demographics and correcting for multiple-hypothesis testing using the Benjamini-Hochberg procedure. We calculated adjusted probability estimates conditional on the presence of no, one, or all protective factors significantly associated with reduced odds of at least three forms of violence in the path model. Adjusted risk differences (ARDs) and adjusted risk ratios (ARRs) with 95% confidence intervals (CIs) were also calculated. The sample mean age was 13.54 years, and 56.62% were female. There was 4% loss to follow-up. Positive parenting, parental monitoring and supervision, and food security at home were each associated with lower odds of three or more violence outcomes (p < 0.05). For girls, the adjusted probability of violence outcomes was estimated to be lower if all three of these factors were present, as compared to none of them: sexual abuse, 5.38% and 1.64% (ARD: -3.74% points, 95% CI -5.31 to -2.16, p < 0.001); transactional sexual exploitation, 10.07% and 4.84% (ARD: -5.23% points, 95% CI -7.26 to -3.20, p < 0.001); physical abuse, 38.58% and 23.85% (ARD: -14.72% points, 95% CI -19.11 to -10.33, p < 0.001); emotional abuse, 25.39% and 12.98% (ARD: -12.41% points, 95% CI -16.00 to -8.83, p < 0.001); community violence victimisation, 36.25% and 28.37% (ARD: -7.87% points, 95% CI -11.98 to -3.76, p < 0.001); and youth lawbreaking, 18.90% and 11.61% (ARD: -7.30% points, 95% CI -10.50 to -4.09, p < 0.001). For boys, the adjusted probability of violence outcomes was also estimated to be lower if all three factors were present, as compared to none of them: sexual abuse, 2.39% to 1.80% (ARD: -0.59% points, 95% CI -2.24 to 1.05, p = 0.482); transactional sexual exploitation, 6.97% to 4.55% (ARD: -2.42% points, 95% CI -4.77 to -0.08, p = 0.043); physical abuse from 37.19% to 25.44% (ARD: -11.74% points, 95% CI -16.91 to -6.58, p < 0.001); emotional abuse from 23.72% to 10.72% (ARD: -13.00% points, 95% CI -17.04 to -8.95, p < 0.001); community violence victimisation from 41.28% to 35.41% (ARD: -5.87% points, 95% CI -10.98 to -0.75, p = 0.025); and youth lawbreaking from 22.44% to 14.98% (ARD -7.46% points, 95% CI -11.57 to -3.35, p < 0.001). Key limitations were risk of residual confounding and not having information on protective factors related to all seven INSPIRE strategies. Conclusion In this cohort study, we found that positive and supervisory caregiving and food security at home are associated with reduced risk of multiple forms of violence against children. The presence of all three of these factors may be linked to greater risk reduction as compared to the presence of one or none of these factors. Policies promoting action on positive and supervisory caregiving and food security at home are likely to support further efficiencies in the delivery of INSPIRE.